Syllidae Grube, 1850 (Annelida) from Southern Africa. A taxonomic update, with a focus on Syllis Lamarck, 1818 - Sedick, Safiyya (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.